MicroRNA-transcription factor network analysis reveals miRNAs cooperatively suppress RORA in oral squamous cell carcinoma. (October 2018) - Zheng, Xueqing; Wu, Kejing; Liao, Shengjie; Pan, Yuemei; Sun, Yanan; Chen, Xinming; Zhang, Yi; Xia, Shu; Hu, Yaying; Zhang, Jiali
Abstract Oral squamous cell carcinoma (OSCC) represents over 90% of oral cancer incidence, while its mechanisms of tumorigenesis remain poorly characterized. In this study, we applied RNA-seq and microRNA-seq methodologies in four pairs of cancer and adjacent normal tissues to profile the contribution of miRNAs to tumorigenesis-altered functional pathways by constructing a comprehensive miRNA-mediated mRNA regulatory network. There were 213 differentially expressed (DE) miRNAs and 2172 DE mRNAs with the involvement of negative miRNA-mRNA interactions identified by at least two pairs of cancerous tissues. GO analysis revealed that the upregulated microRNAs significantly contributed to a global down-regulation of a number of transcription factors (TFs) in OSCC. Among the negative regulatory networks between the selected miRNAs (133) and TFs (167), circadian rhythm genes (RORA, RORB, RORC, andCLOCK ) simultaneously regulated by multiple microRNAs were of particular interest. For instance, RORA transcript was predicted to be targeted by 25 co-upregulated miRNAs, of which, miR-503-5p, miR-450b-5p, miR-27a-3p, miR-181a-5p and miR-183-5p were further validated to directly target RORA, resulting in a stronger effect on RORA suppression together. In addition, we showed that the mRNA and protein expression levels of RORα were significantly decreased in most OSCC samples, associated with advanced clinical stage and poor prognosis. RORα significantly suppressed the proliferation of OSCC cells in vitro and in vivo. Attenuated RORα decreased p53 protein expression and suppressed p53 phosphorylation activity. Altogether, our results strongly suggest the importance of the role of miRNAs in regulating the activity of circadian rhythm-related TFs network during OSCC tumorigenesis, and provide further clues to understand the clinical link between circadian rhythm and cancer therapy.